Habits of Beauty. Towards a “Hexiologia Aesthetica” in the Early Modern Age - Nannini, Alessandro (Aisthesis, 2024)
In this paper I make a case that the identity of disciplinary aesthetics in its inception is grounded in the habituation of αἴσθησις rather than in αἴσθησις as mere epistemic apprehension. To do so, I examine how disciplinary aesthetics arose within the revival of habitus and intellectual virtues in the early modern age, and argue that its ultimate goal was to develop beauty as a specific set of habitus of sensibility. Accordingly, I interpret Baumgarten’s doctrine of the six perfections of sensible knowledge as guidelines of ascetic pathways aimed at restoring the health of the lower faculties of the soul. While the internalization of habitus gives identity to the aesthetic subject, I conclude, this identity takes life only if «inspired», hence in a fruitful exchange with the environment in which the subject is embedded, and in general with the whole universe. In this sense, nascent aesthetics is both ascetic and environmental.